2022
DOI: 10.1371/journal.pgen.1010002
|View full text |Cite
|
Sign up to set email alerts
|

Preformation and epigenesis converge to specify primordial germ cell fate in the early Drosophila embryo

Abstract: A critical step in animal development is the specification of primordial germ cells (PGCs), the precursors of the germline. Two seemingly mutually exclusive mechanisms are implemented across the animal kingdom: epigenesis and preformation. In epigenesis, PGC specification is non-autonomous and depends on extrinsic signaling pathways. The BMP pathway provides the key PGC specification signals in mammals. Preformation is autonomous and mediated by determinants localized within PGCs. In Drosophila, a classic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 80 publications
2
11
0
Order By: Relevance
“…The failure to incorporate the full complement of germline determinants is responsible at least in part for the PGC phenotypes observed in the zld and clamp RNA knockdowns. Consistent with this conclusion, similar PGC phenotypes are observed in gcl mutants and in mutants in components of the BMP signaling pathway (Colonnetta et al, 2021b;Colonnetta et al, 2022). In both of these cases, germline determinants are not efficiently captured by the cellularizing PGCs.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The failure to incorporate the full complement of germline determinants is responsible at least in part for the PGC phenotypes observed in the zld and clamp RNA knockdowns. Consistent with this conclusion, similar PGC phenotypes are observed in gcl mutants and in mutants in components of the BMP signaling pathway (Colonnetta et al, 2021b;Colonnetta et al, 2022). In both of these cases, germline determinants are not efficiently captured by the cellularizing PGCs.…”
Section: Discussionmentioning
confidence: 57%
“…In one model, one or more genes expressed during the minor wave could be important in directing the process of PGC cellularization. This is a plausible mechanism as previous studies have shown that PGC formation and proper specification in early embryos depends upon zygotic activity of the BMP pathway (Colonnetta et al, 2022). For example, when dpp expression is inhibited by zygotic RNAi knockdown, germline determinants like gcl and pgc mRNAs, are not fully captured by the PGCs when they cellularize.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The existence of a shared genetic identity in metazoan spermatocytes can be regarded as a ramification of an ancestral multipotency program already present in germ line precursor cells 54 . Indeed, even in species with divergent germ line segregation strategies, conserved functional interactions at the post-translational level are required for primordial germ cell specification 55,56 . The observation that metazoan chromosomes have deeply conserved gene linkages, some stretching as far back as unicellular organisms, provides a plausible mechanistic basis for the persistence of ancient transcriptional programs 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that the proper specification of PGC identity in flies is not exclusively determined by preformation-based mechanism. Instead, it also depends upon extrinsic somatic signals from the BMP pathway (bone morphogenetic protein pathway) ligand Dpp (Decapentaplegi c ) which is expressed in the early embryo ( Colonnetta et al, 2022 ). For these reasons, we wondered whether the chromatin factors that set the stage for the major wave of ZGA in NC14 also impact the process of PGC specification in early blastoderm embryos.…”
Section: Introductionmentioning
confidence: 99%